Development of Regional Strategic Framework for Nutrition Action Plan as a tool for Health and Nutrition Diplomacy of the Prevention of Non-Communicable Disease (NCD) in ASEAN Countries - Sugeng Eko Irianto; Yudhinanto Yudhinanto (Journal for Quality in Public Health, 2020)
The trend of prevalence of Non-Communicable Diseases (NCD) such as hypertension, cardiovascular diseases, diabetes mellitus, and cancer has increased for the last few decades among low and midle income-countries including Indonesia. Based on the results of Basic Health Resarch performed in Indonesia in 2013, the prevalence of hypertension was 25.8 %, diabetes mellitus was 6.9 %, central obesity was 26.6 %, and stroke was 1.2 %. The cause of NCD is multi-factorial and the main risk factors are high consumption of sugar, salt, and fat, low consumption of vegetables and fruit, overweight, lack of physical activity, and smoking habit. Lower income countries such as Indonesia are beginning to experience disease patterns like high-income countries, as more processed foods are incorporated into diets in a nutrition transition, with less of the necessary healthcare resources to cope with increased disease burden. Globally, obesity or Body Mass Index (BMI) greater than 30 kg/m2 was estimated to have been the cause of 3.4 million deaths in 2010. Excess sugar consumption, particularly consumption of sugar-sweetened beverages (SSBs) is a well- documented, significant causal factor for weight gain. Several studies have found increases in BMI per additional daily serve of SSB and decreases in BMI when SSB consumption is reduced. Excess body mass is a significant risk factor for many NCDs such as ischemic heart disease (IHD), stroke, type 2 diabetes mellitus (T2DM) and various cancers, with the associated morbidity and mortality contributing to rising healthcare costs and reduced productivity. Excess sugar consumption directly increases the risk of T2DM, mediated through both the risk due to higher weight and directly through inflammatory mechanisms triggered by elevated blood sugars.